KEEFEKTIFAN PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN CTL DAN PROBLEM POSING DITINJAU DARI KETERCAPAIAN SK/KD DAN KEMAMPUAN KONEKSI MATEMATIK - Rizky Oktora Prihadini Eka Putri (JURNAL PENDIDIKAN DASAR, 2014)
Abstract: The aims of this research are to describe the effectiveness of the CTL approach viewed from students achievement in SK/KD and mathematics connection ability, describe the effectiveness of the problem posing approach viewed from students achievement in SK/KD and mathematics connection ability, and determine which one is more effective between the CTL approach and the problem posing approach viewed from the students achievement in SK/KD and mathematics connection ability. This research was a quasi-experiment with apretest-posttest non- equivalent group design. The research population covered the entire students of class VII of SMP Negeri 11 Yogyakarta. Classes of VIIA and VIIB were established as the sample using the random sampling technique. To test the effectiveness of mathematics teaching using the CTL approach and the problem posing approach, the analysis of one sample t-test was used. Furthermore, to discover the difference between the effectiveness of mathematics teaching using the CTL approach and the problem posing approach, the data were analyzed using T2Hotellingstest, and t test to determine which approach was more effective. The research result suggests that the CTL approach is effective viewed from the students achievement in SK/KD and mathematics connection ability, the problem posing approach is effective viewed from the students achievement in SK/KD and mathematics connection ability, and the CTL approach is more effective than the problem posing approach viewed from the students achievement in SK/KD, and mathematics connection ability. Keywords: contextual teaching and learning (CTL) approach, problem posing approach, achivement of SK/KD, and students mathematics connection ability.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan keefektifan pendekatan CTL ditinjau dari ketercapaian SK/KD dan kemampuan koneksi matematik siswa, mendeskripsikan keefektifan pendekatan problem posing ditinjau dari ketercapaian SK/KD dan kemampuan koneksi matematik siswa, dan menentukan mana yang lebih efektif antara pendekatan CTL atau pendekatan problem posing ditinjau dari ketercapaian SK/KD dan kemampuan koneksi matematik siswa. Penelitian ini adalah penelitian eksperimen semu dengan desain pretest-posttest non-equivalent group design. Populasi penelitian mencakup seluruh siswa kelas VII SMP Negeri 11 Yogyakarta. Kelas VIIA dan VIIB ditentukan sebagai sampel menggunakan random sampling technique.Untuk menguji keefektifan pembelajaran matematika dengan pendekatan CTL dan problem posing digunakan analisis one sample t-test. Selanjutnya untuk mengetahui perbedaan keefektifan pembelajaran matematika dengan pendekatan CTL dan problem posing, data dianalisis dengan menggunakan uji T2 Hotellings, dan uji t untuk menentukan pendekatan yang lebih efektif. Hasil penelitian menunjukkan bahwa pendekatan CTL efektif ditinjau dari ketercapaian SK/KD dan kemampuan koneksi matematik siswa, pendekatan problem posing efektif ditinjau dari ketercapaian SK/KD dan kemampuan koneksi matematik siswa, dan pendekatan CTL lebih efektif daripada pendekatan problem posing ditinjau dari ketercapaian SK/KD, dan kemampuan koneksi matematik siswa.Kata Kunci: pendekatan contextual teaching and learning (CTL), pendekatan problem posing, ketercapaian SK/KD, dan kemampuan koneksi matematik siswa.